Osteoporosis – diagnostics and treatment - Stachowiak, Grzegorz; Surkont, Grzegorz; Połać, Ireneusz; Jędrzejczyk, Sławomir; Pertyński, Tomasz; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2004)
Osteoporosis is defined as a systemic skeletal disease characterized by low bone mass and micoarchitectural deterioration of bone tissue, with a subsequent increase in bone fragility and susceptibility to fracture. In this paper some facts concerned with etiology, diagnostics and treatment of osteoporosis are presented.